Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Hotel Holiday Inn Kemayoran, Jakarta - Khaisya Nur Haliza; Heribertus Jani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of leadership style and organizational culture on employee performance at Holiday Inn Kemayoran Jakarta. This study uses a field research method with a quantitative approach. This research was conducted with the employee analysis unit of Hotel Holiday Inn Kemayoran Jakarta, with a sample of 50 people. The sampling method used is non-probability sampling with saturation sampling technique obtained by 50 respondents, the data collection technique is a questionnaire. The data processing method uses validity test, reliability test, classical assumption test, and hypothesis test using spss version 26. tcount 0,916 < ttable 2,01174. Organizational culture has an effect on employee performance partially with the results of the t test, namely the significance value of 0.000 <0.05 and the tcount value of 5.437 > ttable 2.01174. Leadership style and organizational culture affect employee performance simultaneously with the results of the f test, namely the significance value of 0.000 <0.05 and the Fcount 37.562> Ftable 3.19.